Bounty Trail - Wheeler, Richard (Thorndike Press, 2004)
Some know him as the Colonel. Some know him as the Most Reverend Archbishop Raines. But from California to Colorado, everyone who meets C. P. Raines thinks he's the most charming, daring, and greedy swindler ever to ply the frontier. Now, this handsome devil with an aversion to work and a God-given talent for fakery has found a little piece of heaven - in a desolate corner of Nevada.
85732
Keywords: Swindlers and swindling; Nevada